Drug utilisation across occupations among pregnant women working in the healthcare and social assistance sector in France: a nationwide population-based study - Mélanie Araujo; Justine Bénévent; Christine Damase-Michel; Yolande Esquirol; Anna-Belle Beau (Occupational and Environmental Medicine, 2026)
Objectives Medication use during pregnancy is common, but patterns may differ across occupational subgroups, particularly in healthcare and social assistance where working conditions, education and health literacy vary. We aimed to compare medications dispensed to pregnant women across occupations within this sector. Methods We conducted a nationwide population-based study using the French EDP-Santé database, linking occupational and socioeconomic data with healthcare reimbursement records. Pregnancies from 2009 to 2015 among women aged 15–55 years were identified. Medication dispensing during the year before and during pregnancy was described by occupational groups using the Anatomical Therapeutic Chemical classification. Comparisons were performed within healthcare occupations. Results Among 321 569 pregnancies, 38 860 (12%) involved women in healthcare and social assistance. Before pregnancy, 91%–95% received at least one medication (mean: 8–12). Psychotropic medication (including antidepressants and benzodiazepines) dispensing was higher among hospital service workers (18% (95% CI 17% to 19%)), healthcare assistants (16% (95% CI 15% to 16%)) and social workers (14% (95% CI 13% to 15%)) than among physicians (11% (95% CI 10% to 13%)), rehabilitation professionals (10% (95% CI 8% to 12%)) and nurses (10% (95% CI 9% to 10%)). Similar patterns were observed for analgesic and musculoskeletal medications. During pregnancy, differences were less pronounced. Folic acid, recommended before and early in pregnancy, was lower among hospital service workers (30% (95% CI 29% to 32%)) than other healthcare workers (39% to 53%). Conclusion Medication dispensing is common among pregnant healthcare workers, with marked variation across occupations. These differences may reflect disparities in working conditions or socioeconomic status, underlining the need for tailored maternal health support in specific occupational groups.